2021
DOI: 10.1039/d0ew01007c
|View full text |Cite
|
Sign up to set email alerts
|

Effects of peracetic acid on aromatic polyamide nanofiltration membranes: a comparative study with chlorine

Abstract: Peracetic acid (PAA) is being considered as a disinfectant in membrane-based wastewater reuse systems. This study shows that PAA is overall compatible with polyamide membranes and proposes PAA-polyamide reaction mechanisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 68 publications
2
16
0
Order By: Relevance
“…Sodium hypochlorite (5% available chlorine, Ricca Chemical Company) and peracetic acid (32 wt % in dilute acetic acid, 5.4 wt % H 2 O 2 , Sigma-Aldrich) were stored at 4 °C. Further, a recent study showed that the loss of polyamide membrane performance by PAA is not accelerated in the presence of ferrous iron, at either low or high H 2 O 2 /PAA ratios. Therefore, in this present study, we did not employ iron-containing solutions to avoid the additional mass (from ions) during QCM measurements.…”
Section: Methodsmentioning
confidence: 98%
See 3 more Smart Citations
“…Sodium hypochlorite (5% available chlorine, Ricca Chemical Company) and peracetic acid (32 wt % in dilute acetic acid, 5.4 wt % H 2 O 2 , Sigma-Aldrich) were stored at 4 °C. Further, a recent study showed that the loss of polyamide membrane performance by PAA is not accelerated in the presence of ferrous iron, at either low or high H 2 O 2 /PAA ratios. Therefore, in this present study, we did not employ iron-containing solutions to avoid the additional mass (from ions) during QCM measurements.…”
Section: Methodsmentioning
confidence: 98%
“…Recently, peracetic acid (PAA), an organic peroxide, is proposed as a promising oxidant for membrane cleaning. , PAA has approximately 100-fold greater disinfection strength than H 2 O 2 and exhibits comparable bacterial inactivation as free chlorine in laboratory-based and pilot-scale , studies. To date, only two studies examined PAA interactions with polyamide using commercial membranes. , No significant change in membrane performance was observed upon PAA exposure up to 180 g h L –1 . In addition, unlike H 2 O 2 , PAA does not accelerate the deterioration of membrane performance in the presence of iron .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This fact, together with the need to counteract the growth of colloidal structures inside IEM and on its surface, necessitate regular cleaning of membrane stacks of ED apparatuses [26]. Most often, HCl, NaOH, hypochlorides and other oxidants (peracetic acid, and P3 Active Oxonia ® (Ecolab, Saint Paul, MN, USA) solutions) are used for these purposes [27][28][29][30][31][32][33][34]. Moreover, cleaning is carried out at a high temperature (60-90 • C) [35][36][37].…”
Section: Impact Of Traditional Cleaning Methods On the Chemical Structure Of Iemsmentioning
confidence: 99%